Effect of Plant Extracts as Seed Treatments on Growth Parameters, Seedlings Mortality and Biochemical Changes in Tomato - Arzoo, Kahkashan; Biswas, S. K. (International Journal of Bio-resource and Stress Management, 2023)
The extract of plant parts like bark of Eucalyptus lanceolotus, Terminalia arjuna, tubers of Cyperus rotundus, leaves of Withamia sominifera, Azadirachta indica, Datura stromonium, Acacia arabica, Cymbopogon flexosus and Parthenium hysterophorus, cloves of Allium sativum, bulb of Allium cepa, fruits of Emblica officinalis and rhizome of Zingiber officinale as seed treatment was found that all the plant extracts significantly increased seed germination and growth of tomato plant both on glass house and laboratory condition by Blotter method. Biochemical analysis of plant extract treated seedlings showed that there was increase in the level of total soluble protein and total phenols content as compared to healthy and diseased plant. The mortality % of tomato seedlings was also reduced in all plant extract treated seedling. The minimum mortality per cent with 5.62 was found in garlic extract treated plant against 80.92% in case of control 2.